Kualitas Pelayanan Kesehatan bagi Peserta Program BPJS Kesehatan Di Puskesmas Tirto II Berdasarkan Asas-asas Umum Pemerintahan yang Baik - Maghfiroh, Atika (Manabia: Journal of Constitutional Law, 2024)
Service standards are benchmarks used as a basis for service delivery and as a reference for assessing service quality in realizing services that are swift, easy, affordable, quality and measurable. Article 3 paragraph (5) of the Regulation of the Minister of Health of the Republic of Indonesia Number 43 of 2019 concerning Public Health, states that community health centers provide health services that are accessible and affordable to all people in their working areas. Article 2 of Pekalongan Regency Regional Regulation Number 12 of 2019 concerning Health Services states that this regulation guarantees that the public will receive health services with quality health facilities and services, to create good quality health, health services must have Standard Operating Procedures (SOP). The case that occurred lies in one of the SOPs available at the Tirto Community Health Center services, namely the SOP for Initial Klimis Assessment. An initial clinical assessment is an activity carried out by a patient with a doctor/paramedic to collect the patient's complete condition, including anamnesis, physical examination and supporting examinations as well as a review of the patient's questions. The difference in the quality of service received by BPJS Health patients is not as complete as that received by non-BPJS patients who receive better and more complete quality of service. In this research the author focuses on 3 general principles of good government. namely the principle of good service, the principle of justice and the principle of non-discrimination. This research is empirical juridical research which uses a statutory approach, case approach and conceptual approach, with data collected from primary and secondary legal materials.